Canada in Question: Federalism in the Seventies - Covert, David (1977)
Canada in Question is an apt title for D. V. Smiley's book discussing federalism in the seventies and the future of the Canadian federalist system. In this second edition, not only does he incorporate recent developments but he expands and re-casts several chapters in order to provide the reader with a more comprehensive coverage of the Canadian federal system. Smiley, in the first seven chapters, deals almost exclusively with the structures and processes of Canadian federalism, whereas the final three chapters are devoted to what he terms a more speculative analysis of the relations between these structures and processes (p. 184). Through use of this format, he is able to present a broad spectrum of issues defining and analyzing the nature of Canadian federalism. Since the coverage is so extensive, depth is sometimes sacrificed to the broader discussion. It is, however, an excellent book for those wishing a survey of the Canadian constitution and the nature of the federalism that has developed from this constitutional framework. Although Smiley recognizes the important influence of the judiciary, his primary focus is on the effects of institutional and governmental interaction on the nature of Canadian federalism